1997
DOI: 10.1046/j.1469-8137.1997.00780.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth, phosphorus uptake, and water relations of safflower and wheat infected with an arbuscular mycorrhizal fungus

Abstract: SafHower (Carthamus tinctorius L. cv. S5S5) and spring wheat {Triticiim aestivum L. cv. Anza) were grown with or without the arbuscular mycorrhizal fungus Glortius ettinicatum Becker & Gerd., under environmentally controlled conditions. Soil phosphate concentrations were adjusted before planting to produce mycorrhizal (M) and non-mycorrhizal (NM) plants that had similar leaf areas and root length densities at the same stage of development before initiating drought stress treatments. Drought did not afTect the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
2
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 43 publications
1
31
2
1
Order By: Relevance
“…However, arbuscles formation did not recover in rewatered plants, probably because arbuscles are assimilated by root cells and their contents are absorbed by the host more rapidly under stress conditions (Kaspari, 1973). While some authors found that water stress affects mycorrhizal symbiotic establishment (Davies et al, 2002;Goicoechea et al, 2005), others such as Bryla and Duniway (1997) reported that drought stress (Ψ s = -1.5 to -2 MPa) does not affect mycorrhizal colonization rates in wheat. Braunberger et al (1994) determined that the hyphae network of AMF , moderate water stress (MoSt), severe water stress (SeSt), moderate water stress followed by rewatering (MoRw) or severe water stress followed by rewatering (SeRw).…”
Section: Discussionmentioning
confidence: 94%
“…However, arbuscles formation did not recover in rewatered plants, probably because arbuscles are assimilated by root cells and their contents are absorbed by the host more rapidly under stress conditions (Kaspari, 1973). While some authors found that water stress affects mycorrhizal symbiotic establishment (Davies et al, 2002;Goicoechea et al, 2005), others such as Bryla and Duniway (1997) reported that drought stress (Ψ s = -1.5 to -2 MPa) does not affect mycorrhizal colonization rates in wheat. Braunberger et al (1994) determined that the hyphae network of AMF , moderate water stress (MoSt), severe water stress (SeSt), moderate water stress followed by rewatering (MoRw) or severe water stress followed by rewatering (SeRw).…”
Section: Discussionmentioning
confidence: 94%
“…Aucune différence significative n'a été enregistrée au niveau du potentiel osmotique chez les plantes témoins et celles qui ont été inoculées. Ces résultats sont similaires à ceux obtenus par plusieurs auteurs [6,12,17,18] [7,43]. Les teneurs en K, Mg et en Na ne sont cependant pas améliorées chez les plantes mycorhizées par rapport à celles non mycorhizées, ce qui pourrait être dû à la forte stimulation de la production de la matière sèche des trèfles mycorhizées.…”
Section: Discussionunclassified
“…Although the benefit of colonization by AMF to plant-water relations has been supported by many studies, the debate still continues. For instance, Bryla and Duniway (1997) observed no AMF effects on osmotic adjustment of DS plants. A similar result was also found by Augé et al (1992) and Goicoechea et al (1997b).…”
Section: Introductionmentioning
confidence: 94%